Solidarity Beyond City Halls: A Study of City Transnational Activism on Palestine Question - Luerdi Luerdi; Arie Fitria; Gita Karisma (INDO PUBLISHING, 2026)
Global communities have been responding to the decades of Palestine-Israel conflict through, for example, transnational activism in solidarity with the Palestinian cause. Cities are now becoming increasingly important in global politics, and they are hardly ignoring international issues, including the imbalanced conflict between two political entities. Despite this, city transnational activism on the Palestine question remains limited in the scholarly realm. This research aimed to investigate transnational activism carried out by several European cities, such as Barcelona (Spain), Oslo (Norway), Liège, and Verviers (Belgium), amidst strong political and military support for Israel from Western countries. The research applied the qualitative method and the concept of city transnational activism. The findings suggest that the selected cities practiced transnational activism in the form of moral calls as well as boycott resolutions to emphasize the necessity to respect Palestinian rights and oppose Israel’s policy towards Palestine and the violation of international law. This paper provides a perspective that local state actors, like cities, through activism, can champion global norms through local actions in response to global issues like conflicts.